Study on the Prevalence and Temporal Shifts of Various Diseases in a Closed Community: A Clinical Study from a Public Sector University - Rafique, Samina; Sarwar, Waseem (Recent Developments in Medicine and Medical Research Vol. 3, 2021)
Epidemiological research is a major concern in the field of public health. Although there is a large number of such studies available from teaching and non-teaching medical institutions (basic health units, rural health centres, and hospitals established at the district level by local government), no such information was available from any public or private university. Therefore, the present study aimed to identify health problems of female students from a public sector university and to find out the temporal variations in the prevalence of these ailments during a year. This will help to select medicines to be available in the pharmacy, allocation of fiscal budget and make a proper guide line for health policy. In this study, the data for more than 4000 female students of age 20 to 25 years coming to Medical Centre of the university during the year 2010 was recorded. The stats were again retrieved for the year 2019 on a similar pattern. The annals for both years indicated that the maximum number of patients was encountered during the 1st quarter of the year. Upper respiratory tract infections were the most common among females, followed by allergic rhinitis/spasm, especially during the winter (December, January, and February) and early spring (March). The prevalence of various ailments and temporal variations were considered to be significant (P< 0.001 for both). A profound upsurge in the prevalence of anemia was noted during the year 2019 and a substantial rise in the frequency of URTIs, allergies, acid peptic disease and GIT infections was observed. The difference in the occurrence of these ailments was significant (p<.001). The study clearly implied that the prevalence of most of the aliments for instance scabies can be attributed to overcrowding and bad personal hygiene. It was also discovered that certain ailments were related to mental tensions such as acid peptic disease, whereas others (anaemia and gastrointestinal disorders) were caused by nutritional imbalance, poor hygienic conditions, and a low quality diet. According to the findings, the community's living conditions should be improved, and mass awareness of personal health and hygiene should be created by involving professionals in lectures and seminars. Furthermore, for efficient operation, the centre should be well-equipped with appropriate diagnostic facilities. Furthermore, an overall increase in health budget is critical to raising the institution's health care standards.